2021
DOI: 10.26603/001c.25168
|View full text |Cite
|
Sign up to set email alerts
|

An Investigation of the Association between Transversus Abdominis Myofascial Structure and Activation with Age in Healthy Adults using Ultrasound Imaging

Abstract: BackgroundBecause of their importance in core stability, training the deep abdominal muscles, fascial structures and particularly the transversus abdominis, is a key component of many sport and physical therapy programs. However, there are gaps in knowledge about age-related changes in the structure and activation capacity of these muscles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 47 publications
(66 reference statements)
1
3
0
Order By: Relevance
“…However, our results also show that young adults had significantly greater relative average TrA thickness than the middle-aged group in all exercises. This finding is consistent with previous research [ 6 , 30 , 31 ] as well as with a systematic review that has shown that younger individuals can recruit TrA higher than older individuals [ 40 ]. Our findings may be explained by several factors, such as differences in neuromuscular control, muscle fiber type composition, or hormonal status between younger and older individuals [ 40 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…However, our results also show that young adults had significantly greater relative average TrA thickness than the middle-aged group in all exercises. This finding is consistent with previous research [ 6 , 30 , 31 ] as well as with a systematic review that has shown that younger individuals can recruit TrA higher than older individuals [ 40 ]. Our findings may be explained by several factors, such as differences in neuromuscular control, muscle fiber type composition, or hormonal status between younger and older individuals [ 40 ].…”
Section: Discussionsupporting
confidence: 93%
“…Previous studies have reported conflicting results on which exercises elicit higher TrA recruitment, such as upper or lower limb lifts from the quadruped position [ 25 ], prone plank [ 26 ], bridge exercises with abdominal bracing [ 27 , 28 ], or planks with opposite arm–leg elevation [ 29 ]. Moreover, some studies have suggested that there may be age-related differences in TrA activation [ 30 , 31 ]. A study by Kellis et al [ 6 ] showed that young adults had the greatest relative transversus abdominis thickness during contraction compared to middle-aged adults, adolescents, and children.…”
Section: Introductionmentioning
confidence: 99%
“…Aging is associated with a decline in muscle thickness, mass and strength, a decrease in muscle fibre volume and an increase in connective tissue, such as the epimysium fascia (Frontera, 2017; Gaudreault et al, 2021; Landi et al, 2017). These changes in the musculoskeletal structure and cells decrease the capacity of muscles to generate force (Şendur et al, 2020), and are also associated with decreased muscle stiffness, which is positively related to the contraction strength of the muscle (Akagi et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have demonstrated that muscle stiffness is significantly higher in younger versus older adults (Do et al, 2021). Gaudreault et al (2021) reported that TrA activation and thickness decreased with age, whereas connective tissue (epimysium fascia) increased, and Davies et al (2016) reported that TrA recruitment in older adults was significantly slower than that in younger adults. Core muscle deterioration also occurs with aging and may contribute to decreased TrA stiffness.…”
Section: Discussionmentioning
confidence: 99%